Tropospheric ozone and skin aging: Results from two German cohort studies. (March 2019) - Fuks, Kateryna B.; Hüls, Anke; Sugiri, Dorothea; Altug, Hicran; Vierkötter, Andrea; Abramson, Michael J.; Goebel, Jan; Wagner, Gert G.; Demuth, Ilja; Krutmann, Jean; Schikowski, Tamara
Abstract: During the last two decades, it has been well established that a short-term exposure to ozone (O3 ) elicits an oxidative stress response in human and mouse skin, which leads to aberrant transcriptional expression of genes consistent with increased skin aging. Whether a long-term exposure to ambient O3 is associated with any skin aging traits, has remained unclear. We addressed this question in two elderly German cohorts: the SALIA study (806 women aged 66–79 years), and the BASE-II study (1207 men and women aged 60–84 years). Five-year mean residential exposure to O3 was modeled as the number of days with maximum daily 8-h mean O3 concentrations ≥120 μg/m 3 per year in the wider neighborhood (5-digit postcode) of a participant's residence. Extrinsic (environmentally induced) skin aging traits – coarse wrinkles and pigment spots (lentigines) on the face – were assessed by means of SCINEXA™, a validated visual score previously shown to be well suited to measure extrinsic facial skin aging in cohort studies. We observed positive associations of O3 exceedances with coarse wrinkles in the face, but not with pigment spots. These associations were present in each cohort as well as in the combined sample of both cohorts. They were independent of chronic ultraviolet radiation exposure as the most obvious confounder, and also of co-pollutants such as particulate matter and nitrogen dioxide. Thus, long-term exposure to elevated concentrations of tropospheric O3 appears to contribute to skin aging. Highlights: Short-term exposure to ozone elicits an oxidative stress response in the skin. It is not clear whether long-term exposure to ozone contributes to skin aging. Ambient ozone concentrations are associated with coarser wrinkles on the face. These findings are independent of ultraviolet radiation and other air pollutants.